Association of Secondhand Smoke Exposure During Pregnancy and Umbilical Cord Blood Vitamin D Levels with Newborn Weight - Izmi Fadhilah Nasution; Delmi Sulastri; Hudila Rifa Karmia (Universitas Islam Negeri Sumatera Utara, Medan, 2023)
Newborn weight is an important predictor of the growth and survival of infants. Low birth weight affects newborns at risk of experiencing health problems and the risk of death Women in developing countries experience many pregnancies with malnutrition, and exposure to cigarette smoke can reduce micronutrient deficiencies. Exposure to cigarette smoke damages the health of pregnant women and their fetuses. Vitamin D is a micronutrient that supports every stage of pregnancy, the placenta, and the fetus to achieve a healthy pregnancy. This study aims to determine the association of secondhand smoke exposure during pregnancy and umbilical cord blood vitamin d levels with newborn weight. This research is a quantitative analytic observational study with a Cross-Sectional Study design. This research was conducted at Hermina Padang Hospital. The time of research was carried out from 14 December 2022 to 10 January 2023. The population in this study were all mothers who gave birth at Hermina Hospital. The sampling technique uses non-probability sampling. The number of samples in this study was 55 samples. Data analysis using the ANOVA test. The study results showed a significant mean difference between the level of exposure to cigarette smoke and birth weight. This can be seen from the p-value <0.05 (p=0.002) and no significant difference in the average blood vitamin D levels. Umbilical cord with birth weight, can be seen from the p-value>0.05 (p=0.484) at Hermina Padang Hospital. It is recommended that health workers provide counseling about exposure to cigarette smoke to pregnant women and mothers to pay attention to meeting the needs of vitamin D during pregnancy. Keywords: Newborn Weight, Secondhand Smoke Exposure, Vitamin D , Newborn Weight